2019
DOI: 10.1016/j.cub.2019.08.032
|View full text |Cite
|
Sign up to set email alerts
|

LLG2/3 Are Co-receptors in BUPS/ANX-RALF Signaling to Regulate Arabidopsis Pollen Tube Integrity

Abstract: In angiosperms, two sperm cells are transported and delivered by the pollen tube to the ovule to achieve double fertilization. Extensive communication takes place between the pollen tube and the female tissues until the sperm cell cargo is ultimately released. During this process, a pollen tube surface-located receptor complex composed of ANXUR1/2 (ANX1/2) and Buddha's Paper Seal 1/2 (BUPS1/2) was reported to control the maintenance of pollen tube integrity by perceiving the autocrine peptide ligands rapid alk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
97
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(107 citation statements)
references
References 60 publications
(102 reference statements)
3
97
0
Order By: Relevance
“…The GO terms give a clear function cluster of RALF-like genes, which involved in the pollen tube development, root development, negative regulation of growth, cell wall growth, hormone activaty, brassinosteroid-mediated signaling pathway, and so on. According to the classification, we found they are very consistent with previous researches about the functions of RALF genes [1,[14][15][16][17][18]64]. Fungal infection response and pollen tube development are important for Rosaceae species, and the RALF-like gene expression in seed and fruit among Rosaceae species specially.…”
Section: Expression Profile Of Ralf-like Genes In Seven Rosaceae Speciessupporting
confidence: 86%
See 3 more Smart Citations
“…The GO terms give a clear function cluster of RALF-like genes, which involved in the pollen tube development, root development, negative regulation of growth, cell wall growth, hormone activaty, brassinosteroid-mediated signaling pathway, and so on. According to the classification, we found they are very consistent with previous researches about the functions of RALF genes [1,[14][15][16][17][18]64]. Fungal infection response and pollen tube development are important for Rosaceae species, and the RALF-like gene expression in seed and fruit among Rosaceae species specially.…”
Section: Expression Profile Of Ralf-like Genes In Seven Rosaceae Speciessupporting
confidence: 86%
“…As reported, RALF genes are not only involved in several biotic and abiotic stresses but also influence the growth and development of plants. Here, we found that the expression profiles are mostly similar with the researchers reported, such as the drought response [13], root growth [64], hormone response [18], fungi response [18][19][20], cell wall development [15,17], and the flower development (especially the development of pollen tube) [14,16]. In the present study, we combined the results of RNA-seq, EST data, cis-regulatory elements analysis, and RT-qPCR to identify several genes which have identical expression profiles in two or more analyses, which may give some instructions of the research of RALF-like genes among Rosaceae species.…”
Section: Expression Profile Of Ralf-like Genes In Seven Rosaceae Speciessupporting
confidence: 85%
See 2 more Smart Citations
“…The polarized, rapid growth of the pollen tube depends on the highly dynamic remodeling of their cell wall. The redundant signaling peptides RALF4 and RALF19 ensure pollen tube integrity and growth by interacting with two distinct protein families, the malectin-domain CrRLK1L membrane receptor kinases (1)(2)(3)(4), and the cell-wall monitoring leucine-rich repeat (LRR) extensin proteins (LRXs) (5,6). Together with ANXUR1/2 and BUDDHA'S PAPER SEAL1/2 (BUPS1/2), the pollen-expressed LORELEI-like GLYCOLPHOSPHATIDYLINOSITOL (GPI)-ANCHORED PROTEINS2 (LLG2) and LLG3 are also required for monitoring pollen tube integrity and are part of the same signaling complex (2,7).…”
mentioning
confidence: 99%